Infill selection for 3D printed radiotherapy immobilisation devices. (29th September 2020) - Asfia, Amirhossein; Deepak, Basaula; Novak, James I; Rolfe, Bernard; Kron, Tomas
Abstract: 3D printing provides new opportunities to create devices used during radiotherapy treatments, yet little is known about the effect process parameters play on the proposed devices. This study investigates the combined influence of infill pattern, infill density and print orientation on surface dose, as well as on the mechanical properties of 3D printed samples, identifying the optimal infill patterns for use in radiotherapy devices including immobilisation. Fused deposition modelling (FDM) was used to produce sixty samples in two orientations for surface dose measurement, utilising ten different infill patterns. Surface dose testing was performed using a Varian Trubeam linear accelerator with a 6 MV photon beam. A further one hundred and twenty tensile test samples, designed according to ASTM D638 type I standards, were evaluated using a 50 KN Instron 5969. On average, horizontally printed samples had a lower surface dose measurement compared to the vertically orientated samples, with the Stars infill pattern recording the lowest surface dose values in the horizontal orientation, while the Hilbert Curve recorded the lowest surface dose in the edge orientation. Tensile tests revealed the 3D Honeycomb infill pattern to have the highest ultimate tensile strength (UTS) in both horizontal and edge orientations. Overall, the Stars infill pattern exhibited the optimal balance of low surface dose and above average UTS. This study shows how infill patterns can significantly affect dosimetry and mechanical performance of 3D printed radiotherapy devices, and the data can be used by design engineers, clinicians and medical physicists to select the appropriate infill pattern, density and print orientation based on the functional requirements of a radiotherapy device.